The Influence of Color and Layout on User Satisfaction in BTN Mobile Banking Application Interface Design - Rizki Ashari; Muhammad Zarlis (Politeknik Siber Cerdika Internasional, 2026)
Background: This research examined how color and layout influenced user satisfaction with the BTN Mobile banking application. The study responded to recurring user concerns regarding navigation clarity, visual consistency, readability, and transaction flow in mobile banking interfaces. Objective: This study aimed to examine the direct effects of color and layout on user satisfaction with the BTN Mobile banking application, investigate the mediating role of perceived UI/UX quality in these relationships, and identify interface usability problems through heuristic evaluation to provide evidence-based recommendations for interface improvement. Methods: A mixed-methods design was applied by combining heuristic evaluation with quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). Questionnaire data were collected from 136 active BTN Mobile users and analyzed using SmartPLS 4, while expert evaluators examined the interface based on usability heuristics. Results: The quantitative results showed that color had a significant direct effect on user satisfaction (p = 0.027), while layout had a stronger significant direct effect on user satisfaction (p < 0.001). However, perceived UI/UX quality did not significantly mediate the effects of color or layout on user satisfaction. The heuristic findings identified 12 usability problems across three severity levels: 3 critical, 5 major, and 4 minor. These problems included inconsistent visual emphasis, low text-to-background contrast, unclear grouping of menu items, and delayed interaction feedback. Conclusion: This study provided practical recommendations for improving BTN Mobile through more accessible color contrast, a more consistent layout hierarchy, clearer navigation grouping, and iterative usability testing.